Valuing and Developing Students’ Creativity - Chuchat, Assoc. Prof. Somchai (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2009)
Creativity and creative teaching are becoming part of the educational psyche but let’s set the concept of creativity within some kind of context. The government is beginning to recognize that young people need to develop the creative skills that will be necessary in the workplace of the future. Fast-moving technology and the increasing demands for flexibility and imagination mean that all our students need to be able to pose questions such as ‘what if…?’, ‘why…?’ and ‘why not?’ It is also more than likely that, as young people start their careers, they will move jobs several times and will need ability to cope with change so that they can produce creative solutions to increasingly complex environments. Creative teaching practices will help prepare them for this-promoting the ability to solve problems, think independently and work flexibly. In Expecting the Unexpected: Developing Creativity in Primary and Secondary Schools (www.ofsted.gov.uk) the Office for Standards in Education (Ofsted) suggests that ‘being creative’ and ‘creative teaching’ are not radical or new concepts-all that they really involve is a willingness to observe, listen and work closely with students to help them develop their ideas in a purposeful way. Ofsted goes on to suggest that it is vital that school leadership is committed to promote creativity because this support and encouragement will permit both students and teachers to work creatively and help to ensure that good practice is recognized, resourced properly and disseminated across the school. It identifies four characteristics of creativity in schools: • thinking and behaving imaginatively • imaginative activities take place in a purposeful way, i.e. related to a specific objective • the activity generates something original • There is value in the activity that is related to the original objective. I think this is an interesting definition when it is applied to teaching and learning because it immediately removes any vague ideas that all creativity is about is lying on summer lawns thinking ‘creative’ thoughts that are never realized. To be able to develop students’ creativity we need to begin with a review of our own attitudes and beliefs and then come up with ideas and specific activities inspiring creativity; these may be complemented with ideas of other people (e.g. exchange ideas, talk to other teachers, go to workshops, read books).